A β1‐6/β1‐3 galactosidase from Bifidobacterium animalis subsp. lactis Bl‐04 gives insight into sub‐specificities of β‐galactoside catabolism within Bifidobacterium. Issue 5 (24th October 2014) - Viborg, Alexander Holm; Fredslund, Folmer; Katayama, Takane; Nielsen, Stinne Kirketerp; Svensson, Birte; Kitaoka, Motomitsu; Lo Leggio, Leila; Abou Hachem, Maher
Summary The Bifidobacterium genus harbours several health promoting members of the gut microbiota. Bifidobacteria display metabolic specialization by preferentially utilizing dietary or host‐derived β‐galactosides. This study investigates the biochemistry and structure of a glycoside hydrolase family 42 (GH42) β‐galactosidase from the probiotic Bifidobacterium animalis subsp. lactis Bl‐04 (BlGal42A). BlGal42A displays a preference for undecorated β1‐6 and β1‐3 linked galactosides and populates a phylogenetic cluster with close bifidobacterial homologues implicated in the utilization of N‐acetyl substituted β1‐3 galactosides from human milk and mucin. A long loop containing an invariant tryptophan in GH42, proposed to bind substrate at subsite + 1, is identified here as specificity signature within this clade of bifidobacterial enzymes. Galactose binding at the subsite − 1 of the active site induced conformational changes resulting in an extra polar interaction and the ordering of a flexible loop that narrows the active site. The amino acid sequence of this loop provides an additional specificity signature within this GH42 clade. The phylogenetic relatedness of enzymes targeting β1‐6 and β1‐3 galactosides likely reflects structural differences between these substrates and β1‐4 galactosides, containing an axial galactosidic bond. These data advance our molecular understanding of the evolution of sub‐specificities that support metabolic specialization in the gut niche.